Hydrodynamic cavitation abrasive finishing - Nagalingam, Arun Prasanth (Nanyang Technological University, 2020)
The production of metal parts via powder bed fusion (PBF) additive manufacturing is rising exponentially. However, the transition of the PBF process from prototyping to production of critical parts such as fuel injectors, conformal cooling channels, and hydraulic manifolds are hindered by a lack of confidence in the surface quality. The poor surface characteristics of PBF components demand post-process surface finishing. The unique surface morphology of PBF components poses several challenges to existing surface finishing techniques. A novel surface finishing technique with dynamic material removal characteristics is required to enhance the internal surface quality. In this thesis, a novel surface finishing process: Hydrodynamic cavitation abrasive finishing (HCAF) was developed. The HCAF technique utilizes the multiphase hydrodynamic principles of high-intense cavitation and microparticle abrasion for surface finishing. The cavitation-assisted microparticle abrasion, a phenomenon that was stated uncontrollable and destructive in the late 1800s, is effectively harnessed for internal surface finishing using a closed-loop hydrodynamic apparatus. The multiphase hydrodynamic flow is harnessed for surface finishing using a pressure-controlled chamber integrated into the HCAF apparatus. First, the hydrodynamic flow characteristics in the HCAF apparatus is extensively characterized using high-speed camera observations and underwater hydrophone sensors. The flow regime transitioned from non-cavitating to cavitation inception, developing and fully developed cavitating phases. From the observations, two configurations: (a) free-stream and (b) submerged; and three modes: (a) hydrodynamic cavitation finishing (HCF), (b) hydrodynamic abrasive finishing (HAF), and (c) hydrodynamic cavitation-assisted abrasive finishing (HCAF) were identified for surface finishing. The root-mean-squared pressure (P_rms) and acoustic energy (E_A) in the non-cavitating conditions were 225 Pa and 47 kJ; in cavitating conditions were up to 6000 Pa and 84 MJ. The significant difference is attributed to the high-intense cavitation microbubble implosion in the fluid medium. Second, a parametric study was conducted to study the influence of cavitation and abrasion on surface finish and material removal characteristics in direct metal laser sintered (DMLS) AlSi10Mg internal channels. The parametric study led to the finding of novel material removal mechanisms in the HCAF process. Material removal mechanisms include #1 – cavitation erosion, #2 – microparticle abrasion, and #3 – cavitation-assisted microparticle abrasion. The maximum calculated impact pressure ( ) = 108 MPa, arising from cavitation bubble implosion, is less than the yield strength of AlSi10Mg alloy (240–270 MPa). Instant material removal of the substrate is unlikely with a single microjet impact. Hence, material removal was caused by low-cycle fatigue, while the surface texture was homogenized (same spatial frequency) through abrasive microcutting. The surface finish quality of the internal channels improved with an increase in hydrodynamic upstream pressure (P_u), abrasive concentration (A_c), fluid temperature (T), and processing time (t). However, the surface quality decreased with increase in downstream pressure (P_d) due to increased cavitation collision with the surrounding bubbles. The surface finish quality of the internal channels improved by greater than 90 % (initial arithmetic mean deviation of the assessed profile (Ra) > 25 µm, maximum height of the assessed profile (Rz) > 100 µm to final Ra < 3 µm, Rz < 30 µm) with a process parametric combination of P_u = 0.7 MPa, P_d = 0.1 MPa, T = 50 ± 2.5 °C, and Ac = 1.0 %. The surface-finish improvement saturated due to the presence of sub-surface defects that kept emerging to the surface with further processing. Third, the surface integrity of the internal channels post-HCAF was investigated. An acceptable thickness loss of 45 µm was noticed with 90 % Ra and Rz improvements. For the microstructure, coarse and irregular grains on the surface (due to loosely attached particles and partially melted powders) were removed; fine and uniform grains (due to fully melted bulk material) were exposed on the surface. Residual stress in the surface was unchanged. However, marginal microhardness improvements (up to 13 %) were noticed. Surface homogenization by microabrasives (abrasive size, A_s = 10 µm) generated a unique microcutting pattern that improved surface wettability by up to 58 %. Moreover, the roughness ratio r ≈ 1 evidenced the uniform and flat surface post-HCAF. Fourth, to gain a deep scientific understanding of the cavitation-assisted microparticle material removal phenomenon, comparative investigations were performed in HAF, HCF, and HCAF modes. The erosion rate (ε ̇) in HCAF was higher than the sum of erosion due to HAF and HCF. Thus, it was understood that a synergistic effect stems out from the interaction between cavitation and microparticles. The synergy (E_s), stemming out from the interaction between cavitation bubble-particle interaction increases the erosion rate by 80 %. The synergy coefficient (β = 1.09 and 0.26 at 0.5 % and 1.0 % Ac) suggests that the rate of increase in synergy decreases with an increase in the abrasive concentration. This is because excessive addition of abrasives alters the fluid properties and suppresses cavitation. Last, an industrial scale multi-jet hydrodynamic cavitation abrasive finishing (MJ-HCAF) apparatus was developed to surface finish large and complex PBF components; decrease processing time; reduce abrasive usage. A case study was performed on PBF Inconel 625 fuel injection/spray nozzles using the MJ-HCAF apparatus. The fuel nozzle geometry is split into linear, non-linear, stepped, and branched internal channels. Internal channels up to a diameter of 1 mm and length 100 mm; non-linear channels with diameter up to1 mm and sharp curvatures; fuel injection tips with four internal branches and spray nozzle tips with five internal branches were surface finished using MJ-HCAF. An excellent surface finish with up to 90 % improvements was achieved in all the channels within 15 minutes of processing. The arithmetic mean height of the scale-limited surface (Sa) and maximum height of the scale-limited surface (Sz) were < 1 µm, and < 20 µm, respectively. The research findings support the hypothesis that cavitation-assisted microparticle abrasion could be used to enhance the surface quality of complex PBF internal channels. The extremely less use of Ac ≤ 1 % weight concentration and eliminating the need to replenish the abrasives using an in-built filtration system makes MJ-HCAF stand out from conventional surface finishing techniques and signifies an emerging class of clean and green manufacturing technology.